Safety, pharmacokinetics, and antitumor properties of anlotinib, an oral multi-target tyrosine kinase inhibitor, in patients with advanced refractory solid tumors. Issue 1 (December 2016) - Sun, Yongkun; Niu, Wei; Du, Feng; Du, Chunxia; Li, Shuting; Wang, Jinwan; Li, Li; Wang, Fengqing; Hao, Yu; Li, Chuan; Chi, Yihebali
Abstract Background Anlotinib is a novel multi-target tyrosine kinase inhibitor that is designed to primarily inhibit VEGFR2/3, FGFR1-4, PDGFR α/β, c-Kit, and Ret. We aimed to evaluate the safety, pharmacokinetics, and antitumor activity of anlotinib in patients with advanced refractory solid tumors. Methods Anlotinib (5–16 mg) was orally administered in patients with solid tumor once a day on two schedules: (1) four consecutive weeks (4/0) or (2) 2-week on/1-week off (2/1). Pharmacokinetic sampling was performed in all patients. Twenty-one patients were further enrolled in an expanded cohort study on the recommended dose and schedule. Preliminary tumor response was also assessed. Results On the 4/0 schedule, dose-limiting toxicity (DLT) was grade 3 hypertension at 10 mg. On the 2/1 schedule, DLT was grade 3 hypertension and grade 3 fatigue at 16 mg. Pharmacokinetic assessment indicated that anlotinib had long elimination half-lives and significant accumulation during multiple oral doses. The 2/1 schedule was selected, with 12 mg once daily as the maximum tolerated dose for the expanding study. Twenty of the 21 patients (with colon adenocarcinoma, non-small cell lung cancer, renal clear cell cancer, medullary thyroid carcinoma, and soft tissue sarcoma) were assessable for antitumor activity of anlotinib: 3 patients had partial response, 14 patients had stable disease including 12 tumor burden shrinkage, and 3 had disease progression. The main serious adverse effects were hypertension, triglyceride elevation, hand-foot skin reaction, and lipase elevation. Conclusions At the dose of 12 mg once daily at the 2/1 schedule, anlotinib displayed manageable toxicity, long circulation, and broad-spectrum antitumor potential, justifying the conduct of further studies.